THE IMPACT OF AI ON ENGLISH PROFICIENCY IN HIGHER EDUCATION - Akmalkhonova S. (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
Artificial Intelligence (AI) has changed English language teaching and learning in higher education, especially in non-native English-speaking countries like Uzbekistan. This article looks at how AI helps improve English skills through personalized learning, instant feedback, and gamified learning environments. Real-world case studies from international universities highlight both the benefits of AI on language performance and the importance of human guidance in its use. The article concludes that AI works best when combined with a balanced educational approach that mixes technology with traditional teaching methods. It stresses the need for both students and educators to understand AI and be aware of ethical issues to ensure effective and sustainable language learning in higher education.